Relationship between explanations of cause of mental illness and the strengthening of being religious - Soewadi Soewadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
The misconception of disease and health of people is influenced by belief In supernatural spirits or magic. This study was designed to contribute to our understanding of the relationship between perceived cause of illness and religious strength. A study was carried out In the Facuity of Medicine Gadjah Mada University, Yogyakarta, Indonesia, among first year students. Data were analyzed using Chi square technique (Mantel Haenszel) and contingency correlation coefficient. The results of the study showed that there was no significant difference between groups of subjects who believed and did not believe in supernatural cause of mental illness according to the religious strength (X2 = 0.88; p>0.05). The results Identified some of the subjects (52.9%) believed in supernatural cause of mental illness and there was also a correlation between such beliefs and the religious strength (C.0 = - 0.13). It was concluded that there was no relationship between perceived cause of mental Illness and the religious strength.Key words : mental Illness - religious - anxiety - mysticism - believe